Mechanical testing methods for body-powered upper-limb prostheses: A review - Mio R. (2018)
New manufacturing and rapid prototyping technologies have fueled the creation of affordable and easy to replicate upper-limb prostheses. In this matter, many types and designs of 3D-printed upper-limb prostheses have been created over the last years. However, there is no consensus in the testing methodology for these devices regarding their mechanical capabilities and the comparisons authors can make are limited to their own metrics, which could be considered as a subjective approach. In order to tackle this issue, this work revises the existing methods for testing both the mechanical resistance and the mechanical performance or efficiency of upper-limb prostheses; specifically, the ones that are relevant for 3D-printed body-powered prostheses. Then, the adaptations needed to apply these methods to 3D-printed prostheses are discussed. Finally, recommendations are given for prosthetists and researchers in order to execute reliable tests that can be compared across different hand prosthesis designs.